1986
DOI: 10.1210/jcem-63-1-125
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hyperthyroidism with a Small Single Daily Dose of Methimazole

Abstract: The duration of action of methimazole (MMI) was studied in patients with hyperthyroidism due to Graves' disease. Perchlorate discharge tests performed 24 h after MMI administration revealed greater than 10% discharge in 77% of 53 patients who received a single dose of 15 mg MMI and in 74% of 23 patients who received 30 mg. The mean percent discharges were 41.5 +/- 26.4% (+/- SD) and 35.4 +/- 28.0, respectively. Based on these results, hyperthyroidism was treated with a single daily dose (SDD) of 15 mg in 43 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 15 publications
6
49
0
2
Order By: Relevance
“…Although the incidence of agranulocytosis with lowdose MMI was one-tenth that of the high-dose regimen, the clinical effectiveness of the regimens was similar [1][2][3]5], suggesting that there is no longer a convincing rationale for continuing high-dose MMI. Despite convincing evidence for the effectiveness of low-dose MMI, many patients referred to our clinic had been placed on high-dose MMI, perhaps because Japanese reference books recommend an initial dose of 30 mg. We do not have data for the other major antithyroid drug, propylthiouracil (PTU), because it is not our first choice for treatment of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the incidence of agranulocytosis with lowdose MMI was one-tenth that of the high-dose regimen, the clinical effectiveness of the regimens was similar [1][2][3]5], suggesting that there is no longer a convincing rationale for continuing high-dose MMI. Despite convincing evidence for the effectiveness of low-dose MMI, many patients referred to our clinic had been placed on high-dose MMI, perhaps because Japanese reference books recommend an initial dose of 30 mg. We do not have data for the other major antithyroid drug, propylthiouracil (PTU), because it is not our first choice for treatment of Graves' disease.…”
Section: Discussionmentioning
confidence: 99%
“…Shirooze et al [1] and Okamura et al [2] reported that the effectiveness of low-dose methimazole (methylmercaptoimidazole; MMI) for the treatment of hyperthyroidism was no less than that of 30 mg MMI. In addition, a European prospective randomized study [3] reported that 10 mg and 40 mg MMI regimens were equally effective.…”
mentioning
confidence: 99%
“…Although the plasma half-life of MMI is about 3-6 h [13,14], the plasma concentration may have little bearing on the duration of its action. MMI is accumulated by the thyroid [15], and a single dose of 15-30 mg of MMI may exert an antithyroid effect for more than 24 h [9,16].…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Shiroozu et al [9] reported that a single daily dose of 15 mg of MMI was as effective as 10 mg administered 3 times daily or 30 mg administered once daily. Several studies have since revealed the efficacy of a small single daily dose of MMI for the initial control of thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Methimazole is used in the treatment of hyperthyroid conditions in humans at doses of 0.2-2 mg/ kg/day po (6,17,31 ). The drug belongs to the thioureylene class of antithyroid drugs, specifically, the thioamides (16).…”
Section: Introductionmentioning
confidence: 99%